Unleashing light's healing power: an overview of photobiomodulation for Alzheimer's treatment - Aakash Ramanishankar; Ankul Singh S; Rukaiah F Begum; Narayanan Jayasankar; Afreen Nayeem; Bhupendra G Prajapati; Shanmugasundaram Nirenjen (Future Science OA)
Aim: Photobiomodulation involves the use of low-level light therapy or near-infrared light therapy found to be useful in the treatment of a wide range of neurological diseases. Objective: The aim is to review the mechanism and clinical applications of photobiomodulation therapy (PBMT) in managing Alzheimer's disease. Methods: To ensure that the consensus statement accurately reflects both the experts' viewpoint and the most recent developments in the field, the expert opinions were recorded and thoroughly reviewed. Results: PBMT elicits reduction of beta-amyloid plaque, restoration of mitochondrial function, anti-inflammatory and antioxidant properties with a stimulation in ATP synthesis. Conclusion: The PBMT could be helpful in patients non-responsive to traditional pharmacological therapy providing significant aid in the management of Alzheimer's disease when introduced into the medical field.